The Covid-19 Era: An Examination of the 5G Conspiracy Theory and the Challenges of Educating Children in Nigeria - Kelechi Johnmary Ani (E-Journal of Humanities, Arts and Social Sciences)
Children are special gifts to parents from God. They were entrusted to their parents and guardians for training and sponsorship into successful adult life. Thus, this study examined the challenges faced by Nigerian children in the era of Covid 19 that ravaged the world. The study used qualitative methodology of secondary data analysis and the 5G Conspiracy Theory to explain how the Covid 19 affected the education of children in the Nigerian setting within the COVID-19 period. It found that parents who aligned themselves with the social conspiracies and social constructivism of the Covid 19, avoided e-forms of educational training for their children and that negatively affected the child-learners as they lost time and necessary intellectual empowerment within that period. It recommends increased use of e-learning platforms to teach children in all government and private teaching establishments in Nigeria.